2020
DOI: 10.1017/s0007114520000586
|View full text |Cite
|
Sign up to set email alerts
|

Effects of linseed oil and rumen undegradable protein:rumen degradable protein ratio on performance of Holstein dairy calves

Abstract: AbstractThe present study evaluated the interaction effects of n-3 fatty acids (from linseed oil (LSO), 0 v. 2·5, % DM basis) with rumen undegradable:degradable protein (RUP:RDP) ratios (low ratio (LR) 27:73; high ratio (HR) 38:62 based on crude protein %) in dairy calves’ starter diet. Forty-eight 3-d-old female Holstein dairy calves (41·5 kg of body weight (BW)) were allocated in a 2 × 2 factorial arrangements in the follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 47 publications
(100 reference statements)
2
23
1
Order By: Relevance
“…Blood insulin concentrations increased in calves fed the SFC diets, which could be related to greater blood glucose concentrations or to greater ruminal VFA concentrations, which have been indicated to be a stimulator for insulin secretion in ruminants (Manns et al, 1967). Regardless of the mechanisms involved in insulin secretion in dairy calves, our results agree with previous reports that stated that greater insulin concentration may influence growth performance of growing ruminants (Wester et al, 2000;Kazemi-Bonchenari et al, 2020).…”
supporting
confidence: 90%
“…Blood insulin concentrations increased in calves fed the SFC diets, which could be related to greater blood glucose concentrations or to greater ruminal VFA concentrations, which have been indicated to be a stimulator for insulin secretion in ruminants (Manns et al, 1967). Regardless of the mechanisms involved in insulin secretion in dairy calves, our results agree with previous reports that stated that greater insulin concentration may influence growth performance of growing ruminants (Wester et al, 2000;Kazemi-Bonchenari et al, 2020).…”
supporting
confidence: 90%
“…Ghasemi et al (38) reported that supplementation with different oil sources did not affect the FE. However, some other studies have noted higher FE in calves fed with C18:3 FA compared to un-supplemented calves (8,36,40) . Although some previous studies used a similar number of animals while evaluating fat sources in dairy calves (38,40,49) .…”
Section: Growth Performance Feed Efficiency and Total Tract Digestimentioning
confidence: 79%
“…Garcia et al (41) have reported that total BW gain by female calves during the first 30 days tended to increase linearly with the increased intake of essential FAs. Kazemi-Bonchenari et al (8) showed that the final BW was greater in calves fed on the LSO rich in n-3…”
Section: Growth Performance Feed Efficiency and Total Tract Digestimentioning
confidence: 99%
See 1 more Smart Citation
“…Sakata et al [ 36 ] suggested that the stimulatory effect of administration of SCFA such as propionate and butyrate into the rumen upon the mitotic index of rumen epithelial cells might be due to an increase in plasma insulin concentration. Higher blood insulin concentration can be also due to increased AA uptake which has been previously proposed in growing lambs [ 37 ] and growing calves [ 38 ].…”
Section: Discussionmentioning
confidence: 98%